Facile One-Pot Synthesis of Diaryliodonium Salts from Arenes and Aryl Iodides with Oxone; ChemistryOpen; Vol. 6, iss. 1 - Soldatova N. S. Nataljya Sergeevna; Postnikov P. S. Pavel Sergeevich; Kukurina O. S. Olga Sergeevna; Zhdankin V. V. Viktor Vladimirovich; Yoshimura A. Akira; Wirth Th. Thomas; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich) (2017, 2017)
Title screen